Exploration, Isolation and Quantification of β-carotene from Bacterial Symbion of Acropora sp. - NAELY K. WUSQY; LEENAWATY LIMANTARA; FERRY F KARWUR (Microbiology Indonesia, 2014)
In the microbial world, pigments are one of the most conspicuous traits. Marine bacteria associated with Acropora sp. collected from Taka Cemara, Karimunjawa Islands were screened for the production of a yellow pigment. The isolation of bacterial symbionts from Acropora sp. on Zobell 2216E medium resulted in one bacterium, KJ5, positively synthesized carotenoids. By reverse phase HPLC analysis, one peak of the pigment types was identified as a β-carotene peak which appeared at 60.24 min. Then, sample of the β-carotene was collected and identified according to their spectral characteristics and compared with the published data in different types of solvent. Based on the HPLC analysis, the total β-carotene contents were calculated by converting the broad absorption of β-carotene. Molecular identification of the bacterium KJ5 using 16S rDNA showed that bacterium KJ5 was closely related to Erythrobacter flavus with 96% homology value.